Extrato de Crambe abyssinica e o constituinte alil isotiocianato no controle de Meloidogyne incognita e Meloidogyne javanica em tomateiro - Roncato, Sidiane Coltro (2015)
The objective of this work was to study the effect of Crambe abyssinica leaf extract on Meloidogyne incognita and Meloidogyne javanica control in tomato plants, and the possible effect of allyl isothiocyanate component in this interaction. Five experiments were conducted. The first experiment was carried out with both Meloidogyne species in vitro: dried leaves of crambe (200 mg L-1) were added in the solvents: water for infusion and grinding, acetone, water + ethanol, methyl alcohol, hexane and chloroform. After the evaporation rotative, the aqueous extracts were analyzed in vitro for nematicide activity (hatching, mortality and motility of second stage juveniles (J2)). After the extracts with increased activity were tested at doses of 200, 300, 400 and 500 mg L-1 of crambe dry leaves. To quantify the allyl isothiocyanate in the extracts was used high performance liquid chromatography (HPLC). The second and third experiment were with M. incognita and hydroalcoholic extract to 250 mg L-1 was used, and each experiment was repeated twice, being the second time with the two best times of the first. The first repetition of the second experiment was conducted in factorial design (3x4+1) in a greenhouse, with three extract application routes: leaf; soil; leaf+soil, in four periods: before inoculation; on inoculation; after inoculation; and weekly up to 45 days and an additional treatment (inoculated and untreated control). In the second repetition, the factorial design was (3x2+1), three routes of application as mentioned above, and two periods (after inoculation and weekly). The third experiment includes the same treatments, however, to the application routes is added the immersion of the tomato roots. The fourth and fifth experiments were with M. javanica, using the same methodology described for the experiments with M. incognita. The results derived from the extracts of hydroalcoholic solution, methanol and trituration were more effective in the action against nematodes, however, the hydroalcoholic one caused higher mortality, with 93% and 64% for M. incognita and M. javanica, respectively. The greatest effect was on the dose of 250 mg L-1, and only the extracts obtained by methanol solution and the hydroalcoholic presented allyl isothiocyanate. When the hydroalcoholic extract was tested in a greenhouse in tomato plants, to M. incognita the applications via soil and weekly did not differ statistically from the applications soil+leaf for the analyzed variables. When the immersion of the tomato plants rooting system was added, weekly applications routes via root+soil and root+soil+leaf stood out, and nematode population in the soil was reduced by 75.55% and 71.95%, respectively, however, the second experiment confirmed the control only to the application via soil+root+leaf. For M. javanica, applications of the extract via soil+leaf weekly caused reduction of total galls on 46.15%. When added the immersion of the root system, the weekly application via root+soil+leaf reduced the egg masses and total galls on 60.95% and 27.95%, respectively. Therefore, crambe extract has potential to make up the integrated management of M. javanica and M. incognita on tomato plants